Reforming the Portuguese mental health system - Perelman, Julian; Chaves, Pedro; de Almeida, José Miguel Caldas; Matias, Maria Ana (International Journal of Mental Health Systems, 2018)
Funding agency: Norway, Iceland (grant nr.00065SM1), Liechtenstein, through the EEA grants and ACSS Background: To promote an effective mental health system, the World Health Organization recommends the involvement of primary care in prevention and treatment of mild diseases and community-based care for serious mental illnesses. Despite a prevalence of lifetime mental health disorders above 30%, Portugal is failing to achieve such recommendations. It was argued that this failure is partly due to inadequate financing mechanisms of mental health care providers. This study proposes an innovative payment model for mental health providers oriented toward incentivising best practices. Methods: We performed a comprehensive review of healthcare providers' payment schemes and their related incentives, and a narrative review of best practices in mental health prevention and care. We designed an alternative payment model, on the basis of the literature, and then we presented it individually, through face-to-face interviews, to a panel of 22 experts with different backgrounds and experience, and from southern and northern Portuguese regions, asking them to comment on the model and provide suggestions. Then, after a first round of interviews, we revised our model, which we presented to experts again for their approval, and provide new suggestions and comments, if deemed necessary. This approach is close to what is generally known as the Delphi technique, although it was not applied in a rigid way. Results: We designed a four-dimension model that focused on (i) the prevention of mental disorders early in life; (ii) the detection of mental disorders in childhood and adolescence; (iii) the implementation of a collaborative stepped care model for depression; and (iv) the integrated community-based care for patients with serious mental illnesses. First, we recommend a bundled payment to primary care practices for the follow-up of children with special needs or at risk under 2 years of age. Second, we propose a ...